Discussion as a method for enhancing communicative skills of university students - Umarkhodjayeva, Dilnoza (The Lingua Spectrum, 2024)
This article explores the use of discussion as a method to enhance communicative skills among university students. It highlights the benefits of active engagement, critical thinking, and collaboration, along with effective strategies for implementing discussion-based learning.